(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Banana inflorescence from Musa acuminata, frequently seen as agricultural waste, is a substantial source of bioactive compounds such as polyphenols and flavonoids. Efficient extraction methods can unlock its potential for functional food. This study aims to evaluate the impact of ethanol as a co-solvent concentration on extract yield, total flavonoid content (TFC), and antioxidant activity. Banana inflorescence was dried using an oven at 60 °C for 4 hours, ground into a fine powder, and stored in vacuum-sealed containers at -20 °C. For maceration, 10 g of the powder was combined with 100 mL of ethanol, agitated for 24 hours, and the ethanol was subsequently evaporated. For supercritical carbon dioxide (scCO₂) extraction, 10 g of powder was extracted using 50% and 100% ethanol as co-solvents under four conditions: 60 °C, 40 MPa; 60 °C, 25 MPa; 40 °C, 40 MPa; and 40 °C, 25 MPa. Extract yield, TFC, and antioxidant activity were measured, with flavonoid content quantified as quercetin equivalents (QE) and antioxidant capacity evaluated using IC50 values. The maximum yield (4.80%) was achieved using scCO₂ extraction with 100% ethanol at 60 °C and 40 MPa, attributed to enhanced solubility at elevated temperature and pressure. TFC was consistently higher with scCO₂ than maceration, reaching 552.94±0.84 mg QE/g using 50% ethanol at 60 °C and 40 MPa due to improved CO₂ density. Antioxidant activity peaked scCO₂ extraction using 100% ethanol at 40 MPa and 40 °C yielding the lowest IC50 (7.97±0.68), indicating superior radical scavenging. These results highlight scCO₂ extraction’s efficacy in maximizing bioactive compounds recovery and antioxidant potential from the banana inflorescence.